Genetically predicted tea intake increases the risk of osteoarthritis: A Mendelian randomization study - Li, Gang; Zhang, Zhe; Liu, Yang (Frontiers in Genetics, 2022)
Background: This study aimed to clarify the relationship between tea consumption and osteoarthritis (OA). Methods: Common single-nucleotide polymorphisms (SNPs) from the Open Genome-wide Association Studies database were obtained. Summary statistics on OA were retrieved from the second dataset that enrolled 50,508 participants (10,083 OA cases) of European ancestry. The causal association between tea intake and OA was tested using two-sample Mendelian randomization (MR) analysis. Results: Tea consumption has adverse effects on OA. (inverse-variance weighted method: OR = 1.19, 95% CI = 1.08–1.30; weighted median method: OR = 1.22, 95% CI = 1.07–1.40). The MR–Egger regression intercept (MR intercept = −0.002; p = 0.73) showed no evidence of directional pleiotropy. Moreover, no evidence of underlying heterogeneity in MR analysis was found according to Cochran’s Q test and funnel and forest analyses. Conclusion: A genetically predicted high daily tea intake can increase the risk of OA.